Influence of La3+ Substitution on Structure, Morphology and Magnetic Properties of Nanocrystalline Ni-Zn Ferrite - Beh , Hoe Guan (2017)
Lanthanum substituted Ni-Zn ferrite nanoparticles (Ni0.5Zn0.5LaxFe1-xO4; 0.00 ≤x≤ 1.00) synthesized by sol-gel method were presented. X-ray diffraction patterns reveal the typical single phase spinel cubic ferrite structure, with the traces of secondary phase for lanthanum substituted nanocrystals